ПОБОРНИК ПРАВА И ЗАКОННОСТИ: АКАДЕМИК ЮРИЙ ТОДЫКА - Аникин, Владимир (SUPREMANCE OF LAW, 2016)
In the material dedicated to the Doctor of juridical sciences, Professor, Academician of the legal rights Yuri Nikolayevich Todyke, is describes his formation as a professional scientist-jurists in Soviet Moldavia. There the main directions of his scientific activity were the issues of improvement of the activity of the Soviets of Public Deputies of all levels, as well as issues related to the legal and regulatory process of agro industrial integration in the Moldavian SSR. Is detailed described about Y N. Todyke activity as the head of the Department of Constitutional Law of the National University “Law Academy named after Yaroslav the Wise” in Kharkov (Ukraine).